Penyalahgunaan Aset: Perspektif Model Fraud Pentagon di Lembaga Keuangan Mikro - Bulan Karima Nurani; Fuad Fuad (Politeknik Ganesha Medan, 2023)
This study aims to obtain empirical evidence regarding the factors behind asset misappropriation in Micro Institutions. The purpose of this research will be achieved by using a quantitative approach and using primary data obtained through the distribution of questionnaires. The populations in this study were 247 employees who work in cooperatives within the Association of Indonesian BMT (PBMTI) Semarang Regency. This research is a census study where the entire population is used as a respondent. The collected data were processed by the Structural Equation Modeling (SEM) analysis method, using the Smart PLS 3.2.9 analysis tool. The results showed that all elements of the Fraud Pentagon Theory had a significant positive effect on asset misappropriation. The implications of this study indicate that the higher opportunity, pressure, rationalization, competence, and arrogance will increase the potential of asset misappropriation; and the fewer opportunity, pressure, rationalization, competence, and arrogance will reduce the possibility of asset misappropriation in cooperatives within the Association of Indonesian BMT (PBMTI) Semarang Regency. Further research is suggested to add other methods such as interviews or direct observation so that information obtained through questionnaires can be confirmed. In addition, although the number of unit analysis in this study was sufficient, the further researcher is expected to coordinate directly with every employee at the branch office or use online questionnaires so the percentage of questionnaire returns can be better.